Development of high strength, high conductivity copper by friction stir processing - Surekha, K.; Els-Botes, A. (Materials in engineering, 2011)
The objective of this study is to obtain a high strength, high conductivity copper by friction stir processing. Three milli meter thick pure copper plate was friction stir processed to a depth of 2.8 mm at low-heat input conditions by varying the travel speed from 50 to 250 mm/min at a constant rotation speed (300 rpm) to obtain fine grains. Grain size of the nugget decreased from 9 to 3 μm and the hardness increased from 102 to 114 H V by increasing the traverse speed from 50 to 250 mm/min. Yield strength, microhardness and ultimate tensile strength increased with decrease in grain size in the nugget region and the yield strength obeyed σ s = 223.8 + 0.07 d −1/2 Hall–Petch relationship, where d is the grain size in m. Electrical resistivity measurement at room temperature showed that there was no change in the resistivity of the processed samples compared to the base metal.